The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/0034-7167-2021-0031
|View full text |Cite|
|
Sign up to set email alerts
|

The family of the child with special health care needs and their social relationships

Abstract: Objectives: to identify aspects that can influence the types of bonds developed in the social support network of family members of children with special health care needs. Methods: qualitative research conducted through interviews with 15 family members/guardians in the city of Rio de Janeiro, from January to February 2020. Sanicola’s theoretical-methodological framework and Bardin’s thematic analysis technique were used. Results: social distancing, lack of responsibility for coordinating care, lack of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Furthermore, recent research has identified that family caregivers can increase the level of stress, anxiety and depressive symptoms ( 10 , 27 ) , and these problems may require psychopharmacological treatment and psychological support ( 24 ) . Furthermore, this situation can be considered as a sign of probable exposure of the child to adverse situations, of insufficiencies in care actions, due to the limitations of caregivers due to their illness ( 23 , 28 ) . Other studies highlighted that family members can even be affected physically (sleep deprivation, tiredness), mentally and financially, with a negative impact on the quality of ongoing care and the functioning of the family as a whole ( 13 , 17 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent research has identified that family caregivers can increase the level of stress, anxiety and depressive symptoms ( 10 , 27 ) , and these problems may require psychopharmacological treatment and psychological support ( 24 ) . Furthermore, this situation can be considered as a sign of probable exposure of the child to adverse situations, of insufficiencies in care actions, due to the limitations of caregivers due to their illness ( 23 , 28 ) . Other studies highlighted that family members can even be affected physically (sleep deprivation, tiredness), mentally and financially, with a negative impact on the quality of ongoing care and the functioning of the family as a whole ( 13 , 17 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, pesquisas recentes identificaram que os cuidadores familiares podem elevar o nível de estresse, ansiedade e sintomas depressivos ( 10 , 27 ) , sendo que os agravos podem requerer tratamento psicofarmacológico e acompanhamento psicológico ( 24 ) . Além disso, a situação pode ser considerada como sinalizadora de provável exposição da criança a situações adversas, de insuficiências nas ações de cuidado, devido à limitação dos cuidadores por seu adoecimento ( 23 , 28 ) . Outros estudos destacaram que os familiares, inclusive, podem ser afetados fisicamente (privação do sono, cansaço), mental e financeiramente, com impacto negativo a qualidade do atendimento contínuo ao funcionamento da família como um todo ( 13 , 17 , 25 ) .…”
Section: Discussionunclassified
“…E o apoio social é definido como um tipo de suporte positivo que os membros da rede social oferecem, seja de origem material, financeira, emocional e/ou psicológica. Além disso, os vínculos estabelecidos com os membros da rede podem ser classificados em forte, normal, frágil, conflituoso ou rompido 13 Os participantes do estudo foram cinco cuidadores de crianças com Síndrome de Down residentes no município do Rio de Janeiro. Para atender os critérios de inclusão, era necessário que o participante fosse o cuidador principal de uma criança com SD que estivesse em acompanhamento no referido Centro de Reabilitação na ocasião do período de coleta de dados.…”
Section: Métodounclassified